Xenophon τακτικός? Remarks on his use of -ικός adjectives: ¿Jenofonte τακτικός? Observaciones sobre su uso de los adjetivos en -ικός - Pontier, Pierre (Araucaria, 2024)
Xenophon’s interest in the art of command has never diminished. This article analyzes his ambivalent relationship with “tactics”, an art he sometimes dissociates himself from, because he considers it to take the place of a much more important knowledge that ultimately encompasses it. This is also demonstrated by his subtle use of -ikos adjectives in both the Memorabilia and the Hellenica. The list of terms, often attested for the first time, confirms that the suffix suggests a specialization and an approach to a limited body of knowledge, but above all demonstrates Xenophon’s singular place in the transmission of military knowledge: he is both close to Aeneas the Tactician, as well as anxious to distinguish himself from these professionals of the military art.